Analysis of The Independent Learning Program In The Independent Campus to Competency of Tadulako University Geography Education Students - Gunawan, I Putu Pasek; Maliki, Rendra Zainal; Saputra, Iwan Alim; Ali, Zaenudin; Putra, Exsa (PAEDAGOGIA, 2023)
This research discusses the impact of the Independent Campus Learning Policy (MBKM) launched by the Indonesian Minister of Education and Culture. MBKM has created a new paradigm in the education system in Indonesia, especially in higher education. Tadulako University, as an educational institution that follows government policy directions, has implemented the MBKM program. In this context, geography education has been implemented and entered the next generation. Therefore, evaluation of the effectiveness of this program is considered important. Previous research has revealed the positive impact of Merdeka Belajar Merdeka Campus on student quality. Student quality involves increasing knowledge, understanding, experience, creativity, communication skills, social relations, adaptability, and problem-solving skills. This study investigates the impact of MBKM activities on students' abilities, particularly in basic competencies such as literacy, numeracy, and geography knowledge. This research method is a descriptive quantitative approach using survey methods. The survey was conducted on students who had participated in the MBKM program. The research instrument is a competency test that involves aspects of literacy, numeracy, and general knowledge of geography. The results showed that the MBKM program had a positive impact on improving student abilities. The geography education study program is also seen as excellent, with a literacy understanding level reaching 50% in the adequate category, a numeracy understanding level of 39% in the adequate category, and a general knowledge understanding level reaching 44% in the good category